Paruyr Sevak and Marina Tsvetaeva - Grigoryan, Seyran (Bulletin of Yerevan University H: Russian Philology, 2021)
The article examines the literary connections between Paruyr Sevak’s poetry and Marina Tsvetaeva’s works. It is shown that Sevak knew Tsvetaeva’s poetry perfectly, highly appreciated it and had been influenced by poetess’s figurative thinking and way of constructing poetic language. The propinquity of Armenian and Russian poet's love lyrics is a matter of special attention. The author concludes that Tsvetaeva’s deep and original art had a indubitable impact on the motivs, philosophy and poetics of Sevak’s works.
Keywords: literary connection, poetic language, motivs, images